Towards a genome-scale metabolic model for the Kluyveromyces lactis yeast - Dias, Oscar (2013)
The interest in Kluyveromyces lactis (K. lactis) has begun in academia due to its ability to metabolize the betaglycoside (1). Since then, this yeast has been considered a model organism for studies in genetics and physiology (2). This yeast had its genome sequenced back in 2004 (3) and recently we have published a full metabolic re-annotation of its genome (4). This re-annotation can be used, among other applications, to reconstruct genome-scale metabolic models. These models allow anticipating a given organism's phenotype from its genome sequence. The reconstruction of biochemical networks is, currently, a valid alternative to microorganisms modelling as the output provided by the in silico simulations permits focusing on experiments with promising results. Thus, we propose a new fully compartmentalised genome-scale metabolic model for K. lactis, the iOD1759 which comprises 1759 metabolic genes.